Terrorist Demonstration of Islam in Daily News in Riau - Aidil Haris; Syukur Kholil; Lahmuddin Lahmuddin (Budapest International Research and Critics University, 2019)
Related to the news about the terrorist case, many opinions confirm that Islam is not a terrorist. Islam never teaches violent behavior in state life. Islam remains Islam and terrorists must burn on earth. The problem that happened was that mass media coverage always tended to link Islam and terrorists. To look more deeply at the agenda of media settings in reporting about Islam and Terrorists, researchers want to see this phenomenon in local media in Riau. From the two major media in Riau, namely Riau Pos and Pekanbaru Tribun, researchers studied more deeply about terrorist labeling of Islam through the perspective of critical and ideological studies which eventually gave rise to assumptions about the concept of labeling mass media in the formation of its agenda. So that an important question emerged which was formulated in this study, namely how the label of terrorists against Islam on news about terrorist cases in Tribun Pekanbaru and Riau Pos daily newspapers. This study uses Fairclough CDA model of the procedure for critical discourse analysis whose stages consist of three, namely description, interpretation and explanation. The research methodology in this research uses qualitative research methodology. Qualitative methodology is more intended to express a picture and / or understanding (understanding) about how and why a phenomenon or reality occurs. Based on the results of the research conducted, it can be seen that the west has succeeded in discussing the labeling of Islam as a terrorist religion through mass media. This is evident from the absence of a review by the editors of the media on the meaning of the word terrorist labeled against Islam in every report about terrorists.